Molecular signatures and mechanisms of long-lasting memory consolidation and storage - Katche, Cynthia Lorena (2013)
A body of evidence emerged in the last decade regarding late posttraining memory processing. Most of this new information comes from aversively motivated learning tasks that mainly depend on hippocampus, amygdala and insular cortex, and points to the involvement of long-lasting changes in gene expression and protein synthesis in late stages of memory consolidation and storage. Here, we describe recent advances in this field and discuss how recurrent rounds of macromolecular synthesis and its regulation might impact long-term memory storage.